1999
DOI: 10.1038/sj.bjc.6690786
|View full text |Cite
|
Sign up to set email alerts
|

Interval cancers in the Dutch breast cancer screening programme

Abstract: SummaryThe nationwide breast cancer screening programme in The Netherlands for women aged 50-69 started in 1989. In our study we assessed the occurrence and stage distribution of interval cancers in women screened during 1990-1993. Records of 0.84 million screened women were linked to the regional cancer registries yielding a follow-up of at least 2.5 years. Age-adjusted incidence rates and relative (proportionate) incidences per tumour size including ductal carcinoma in-situ were calculated for screen-detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
44
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 21 publications
9
44
0
Order By: Relevance
“…Further, discarding DCIS should enhance international comparability of IC by excluding an entity whose classification may differ across pathologists and which is the main contributor to over-diagnosis in screening programmes. On the other hand, inclusion of the DCIS diagnosed in the interscreening interval, which contribute between 2 and 8% of all IC, 7,10,29 implicitly considers opportunistic screening activity as a contributory factor for international differences in IC frequency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, discarding DCIS should enhance international comparability of IC by excluding an entity whose classification may differ across pathologists and which is the main contributor to over-diagnosis in screening programmes. On the other hand, inclusion of the DCIS diagnosed in the interscreening interval, which contribute between 2 and 8% of all IC, 7,10,29 implicitly considers opportunistic screening activity as a contributory factor for international differences in IC frequency.…”
Section: Discussionmentioning
confidence: 99%
“…22 The Dutch programme evaluation takes the loss to follow-up into account for women who died or moved away from their region before their next screening examination, and also the exact date of the next screening examination. 10 IC rates are then expressed as the number of IC divided by the number of women-years of follow-up within the corresponding time period. It is important that the numerator and the denominator refer to the same time span when calculating the incidence of IC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Early assessment after an unclear screening result is discouraged in the Norwegian Breast Cancer Screening Program's quality manual. Women who [15][16][17] However, when the interval was split in 2 periods, comparison of observed/expected ratios revealed that whereas our rate in the first year was in accordance with the reported proportionate incidences, our estimate of the second year (0.75) was higher than the corresponding figures from other programs (0.59 in East Anglia, 14 0.52 in Holland, 15 0.52 in North West England 16 and 0.54 in Victoria, Australia 17 ). In the last 6-month period, the observed/expected ratio approached 1, which indicated that the incidence of interval cancers approached the expected incidence without screening.…”
Section: Frequency Of Invasive Interval Cancersmentioning
confidence: 99%
“…The results were in agreement with results reported from other mammography screening programs with a 2-year screening interval. 15,22 Two Norwegian clinical breast cancer materials from the prescreening period are published. 23,24 The proportion of pT1 (Յ20 mm) tumors and the proportion of patients with affected axillary lymph in these materials were about 40%.…”
Section: Characteristics Of the Interval Cancersmentioning
confidence: 99%